REACTIVE ARTHRITIS ACCOMPANYING SPOROTRICHOSIS POST CAT SCRATCH: A MALAYSIAN CASE REPORT - Jamallulail SI; Wahinuddin S; Abdullah AC (Asian Journal of Medicine & Health Sciences, 2019)
Sporotrichosis is a fungal infection caused by Sporothrix schenckii, a dimorphic fungus. Transmission of this infection is usually through contact with infected soil, decaying vegetation and plants as well as zoonotic inoculation such as cat scratches. We present an uncommon case of lymphocutaneous sporotrichosis accompanied by reactive arthritis in a 51-year-old woman due to a cat scratch in Malaysia.